Analisis Kematian Akibat Demam Berdarah Dengue di Kabupaten Lebak Banten - Nurhasanah, Siti; Jannah, Miftahul; Barokah, Sri (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Dengue hemorrhagic fever (DHF) is a disease caused by dengue virus infection. DHF is an acute disease with clinical manifestations of bleeding which causes shock which leads to death. One of the areas affected by the dengue virus is Lebak Banten district with 1,400 people infected with the dengue virus and 6 people died within a period of 4 months. This is due to changes in weather and the habits of people who do not care about the environment, allowing water to stagnate, giving rise to Aedes Aegypty mosquito larvae. This research uses qualitative research methods with descriptive observational research techniques, namely a research design that aims to only describe phenomena found based on previously existing data without researcher intervention. The results of this research are to understand the problem of the spread of the dengue virus in Lebak district and the collaboration between the government and the local community in controlling it.